Star enclosed circle split ring resonator-based metamaterial sensor for fuel and oil adulteration detection - Md. Rashedul Islam; Mohammad Tariqul Islam; Ahasanul Hoque; Ahmed S. Alshammari; Ahmed Alzamil; Haitham Alsaif; Md. Samsuzzaman; Mohamed S. Soliman (Alexandria Engineering Journal, 2023)
A unique shaped metamaterial sensor is proposed for detecting a wide range of pure and adulterated fuels and oils. The functionality of the designed structure has been examined both theoretically and practically ways, and the results show that it performs incredibly well. A new sample holder is built for more convenient functioning, and it is attached directly behind the constructed structure. In the field of research on liquids sensing, the purpose of this work was to present an alternative methodology. The CST microwave studio software is used to test a variety of different designs to determine which ones would result in the resonator having the best possible dimensions. The resonance frequency shifted 270, 410, and 180 MHz; between pure petrol and a mixture of 20 % kerosene and 80 % petrol, 100 % diesel and a mixture of 20 % ethanol and 80 % diesel, and clean olive oil and a mixture of 20 % corn oil and 80 % olive oil, respectively. The sensor has a quality factor of 430, high sensitivity of 1.99, and a figure of merit of 855.70, which indicates that it performs well and efficiently. In addition, the sensor that has been presented can accurately differentiate between various liquids by making use of the frequency shifting feature. The findings obtained demonstrate that this concept is readily applicable for a wide variety of electrochemical sensing applications even if the permittivity of the sample is altered; this is indicated by the findings. Because the sensor that is recommended possesses high sensitivity, a high-quality factor, and outstanding performance, it is suitable for use in the fuel industry, oil industry, and microfluidics industry.